2017
DOI: 10.3389/fmolb.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

A Simple PB/LIE Free Energy Function Accurately Predicts the Peptide Binding Specificity of the Tiam1 PDZ Domain

Abstract: PDZ domains generally bind short amino acid sequences at the C-terminus of target proteins, and short peptides can be used as inhibitors or model ligands. Here, we used experimental binding assays and molecular dynamics simulations to characterize 51 complexes involving the Tiam1 PDZ domain and to test the performance of a semi-empirical free energy function. The free energy function combined a Poisson-Boltzmann (PB) continuum electrostatic term, a van der Waals interaction energy, and a surface area term. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Conversely, when ID6 was forced to bind a fibril in a nonextended compact conformation, the calculated interaction energy was more than 35 kcal/mol less favorable than the extended conformation (Figure S14). 59,60 Interaction energies were determined for the entire family of IDs and showed that the longer IDs have greater binding potentials (Figure 6A). Interestingly, the interaction energies are much greater than what might be expected for typical electrostatic interactions in proteins (normally on the order of single digit kcal/mol) 29,30 and are more comparable to the energies observed for the complexation of oppositely charged peptide homopolymers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Conversely, when ID6 was forced to bind a fibril in a nonextended compact conformation, the calculated interaction energy was more than 35 kcal/mol less favorable than the extended conformation (Figure S14). 59,60 Interaction energies were determined for the entire family of IDs and showed that the longer IDs have greater binding potentials (Figure 6A). Interestingly, the interaction energies are much greater than what might be expected for typical electrostatic interactions in proteins (normally on the order of single digit kcal/mol) 29,30 and are more comparable to the energies observed for the complexation of oppositely charged peptide homopolymers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…25,27 GB models have been studied extensively in the context of protein design but also molecular dynamics, free energy simulations, acid/base calculations, ligand binding and protein folding. 25,[28][29][30][31][32] They reproduce the behavior of the dielectric continuum model rather accurately. Therefore, an energy function that combines molecular mechanics for the protein with a Generalized Born solvent can be considered "physics-based", even though it is not entirely constructed from first principles.…”
Section: Introductionmentioning
confidence: 93%
“…Computer simulations are a complementary tool, well suited to study solvated proteins, their structure, dynamics, and ligand binding (22)(23)(24)(25)(26). Of particular interest are nonempirical methods that predict binding free energy differences from molecular dynamics (MD) simulations without any adjustable parameters (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…We mostly used the AMBER ff99SB additive force field (32,47). Six of the ff99SB alchemical mutations were reported earlier (26). For four of the ionic mutations, we also used the CHARMM C36 additive force field (33,48) and the CHARMM Drude polarizable force field (44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%